2022
DOI: 10.1155/2022/3177706
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Predicament and Outlet: The Deep Fusion of Information Technology and Political Thought Teaching in Institution of Higher Learning under the Background of Fragmented Learning Environment

Abstract: The ongoing integration of IT with various disciplines is a result of IT’s constant penetration of the educational sector. This paper investigates how to further promote the deep integration of IT and political thought courses in institution of higher learning based on the fragmented learning background, starting from the current teaching situation of political thought courses in institution of higher learning, based on modern educational theory and supported by IT. Strengthening the relevance and affinity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%